A case of empyema and septic arthritis due to Nocardia farcinica. Issue 12 (24th October 2017) - Ishiguro, Takashi; Yoshioka, Hiroaki; Kawai, Shoko; Katsumata, Shin‐ichi; Gonoi, Tohru; Takayanagi, Noboru
Key Clinical Message: Septic arthritis due to Nocardia sp. should be suspected when a patient with risk factors such as pneumoconiosis or diabetes mellitus develops joint symptoms, especially if the patient has had nocardiosis in other sites. Abstract : Septic arthritis due to Nocardia sp. should be suspected when a patient with risk factors such as pneumoconiosis or diabetes mellitus develops joint symptoms, especially if the patient has had nocardiosis in other sites.